Genome assembly of Musa beccarii shows extensive chromosomal rearrangements and genome expansion during evolution of Musaceae genomes - Wang, Zheng-Feng; Rouard, Mathieu; Droc, Gaëtan; Heslop-Harrison, J.S.; Ge, Xue-Jun (Oxford University Press, 2022)
Background